Effectiveness Implementation of Fine Criminal Sanction in Extraordinary Events or Pandemic Outbreak According to the Law Number 17 of 2023 Concerning Health (Health Omnibus Law) - Renfred Valdemar; Rospita Adelina Siregar; Mompang L. Panggabean (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
Pandemic outbreak is a non-natural disaster that is physically invisible and difficult to detect. Along with the experience and high death rate in Covid-19, it has encouraged the Government to issue Law No. 17 of 2023 concerning Health (Health Omnibus Law). Criminalization is the path chosen by the government as a form of state priority for the people in overcoming the spread and transmission of the pandemic outbreak. However, currently there is still a polemic about how legal action uses criminal sanctions during a pandemic. The study was conducted using a descriptive method, which aims to examine the effectiveness of the application of criminal sanctions for anyone who obstructs the implementation of efforts to control pandemic outbreak or violates health protocols. The results of this study indicate that Article 446 of Law No. 17 of 2023 concerning Health (Omnibus Law of Health) is the basis for criminalization for violators of the pandemic outbreak response, with the imposition of a maximum criminal fine of IDR 500,000,000 (Five hundred million Rupiah). With restrictions on movement accompanied by administrative sanctions alone, it has made the people's economy very difficult, especially if it is added to criminal fine. The sense of justice and legal certainty for the community is increasingly absent. The application of criminal sanctions should not be applied during a pandemic, because everyone has the right to maintain their own lives. This only adds to the suffering of people who do not agree with government policies by forcing them to follow health protocol rules that are contrary to their conscience.